Organic Carbon Stock in Sediment of the Rehabilitated Mangrove Ecosystem in Kedabu Rapat Village, Meranti Islands Regency - Cahyo, Bintang Dwi; Efriyeldi, Efriyeldi; Amin, Bintal (Journal of Coastal and Ocean Sciences, 2025)
Global climate change caused by increasing atmospheric CO₂ emissions threatens coastal ecosystems, including mangrove forests that function as carbon sinks. Kedabu Rapat Village in Meranti Islands Regency has implemented a mangrove rehabilitation program since 2017 to overcome coastal abrasion and restore the ecosystem. This study examines mangrove density, organic carbon stock in sediment, the relationship between density and carbon stock, and variations in carbon stock between sediment depths. The study was conducted at three stations according to the year of rehabilitation using a survey method with sediment sampling as deep as 30 cm, Organic carbon was analyzed using the LOI method. The study's results identified one mangrove species, Avicennia alba, from the Acanthaceae family, which dominated all observation stations. Vegetation density is classified as very dense, averaging 7,911 ind/ha, with the highest density at Station 1 (8,935 ind/ha). All stations' average sediment carbon stock reached 117.23 tons/ha, with the highest value at Station 3 (135.19 tons/ha) and the lowest at Station 1 (96.97 tons/ha). Statistical analysis revealed a weak correlation (r = 0.218; p > 0.05) between mangrove density and sediment carbon stock, indicating that other environmental factors, such as sedimentation and sediment input, play a more significant role. The distribution of carbon stock by depth was relatively uniform, ranging from 38.25 to 40.58 tons/ha. These results indicate that external factors are also determinants of carbon absorption rates